Neuroinflammation and Its Impact on the Pathogenesis of COVID-19 - Almutairi, Mohammed M.; Sivandzade, Farzane; Albekairi, Thamer H.; Alqahtani, Faleh; Cucullo, Luca (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The clinical manifestations of COVID-19 include dry cough, difficult breathing, fever, fatigue, and may lead to pneumonia and respiratory failure. There are significant gaps in the current understanding of whether SARS-CoV-2 attacks the CNS directly or through activation of the peripheral immune system and immune cell infiltration. Although the modality of neurological impairments associated with COVID-19 has not been thoroughly investigated, the latest studies have observed that SARS-CoV-2 induces neuroinflammation and may have severe long-term consequences. Here we review the literature on possible cellular and molecular mechanisms of SARS-CoV-2 induced-neuroinflammation. Activation of the innate immune system is associated with increased cytokine levels, chemokines, and free radicals in SARS-CoV-2 induces a pathogenic response at the blood-brain barrier (BBB). BBB disruption allows immune/inflammatory cell infiltration into the CNS, resulting in activation of immune resident cells (such as microglia and astrocytes). This review highlights the molecular and cellular mechanisms involved in COVID-19-induced neuroinflammation, which may lead to neuronal death. A better understanding of these mechanisms will help gain substantial knowledge about the potential role of SARS-CoV-2 in neurological changes and plan possible therapeutic intervention strategies.